2012
DOI: 10.1088/2041-8205/750/1/l1
|View full text |Cite
|
Sign up to set email alerts
|

Large-Amplitude Longitudinal Oscillations in a Solar Filament

Abstract: We have developed the first self-consistent model for the observed large-amplitude oscillations along filament axes that explains the restoring force and damping mechanism. We have investigated the oscillations of multiple threads formed in long, dipped flux tubes through the thermal nonequilibrium process, and found that the oscillation properties predicted by our simulations agree with the observed behavior. We then constructed a model for the large-amplitude longitudinal oscillations that demonstrates that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
95
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 30 publications
16
95
0
1
Order By: Relevance
“…However, here we have found that the temporal evolution of the velocity is given by the sine divided by a linear function of its argument. The phase of the argument is half that found in the case studied by Luna & Karpen (2012). The difference between the two models is in how the hot evaporated mass is deposited in the cool thread.…”
Section: Linear Theory With Strong Dampingmentioning
confidence: 76%
See 3 more Smart Citations
“…However, here we have found that the temporal evolution of the velocity is given by the sine divided by a linear function of its argument. The phase of the argument is half that found in the case studied by Luna & Karpen (2012). The difference between the two models is in how the hot evaporated mass is deposited in the cool thread.…”
Section: Linear Theory With Strong Dampingmentioning
confidence: 76%
“…In addition, Luna & Karpen (2012) and Luna et al (2012a) assumed that the thread filled the dipped part of the flux tube A131, page 4 of 10 meaning that rθ = l p /2. Then taking into account that, for typical prominences, the density contrast is very large meaning that 1 − 1/ζ ∼ 1, we finally arrive at…”
Section: Prominence Oscillations In a Magnetic Tube With Two Straightmentioning
confidence: 99%
See 2 more Smart Citations
“…For the extreme case of a tube with uniform cross-section, the typical distances are infinite. Figure 2 shows the fitted values of ǫ 1 and ǫ 2 for the flux tubes studied by Luna et al (2012b) and Luna & Karpen (2012).…”
Section: Flux Tube Cross-section Modelmentioning
confidence: 99%